Pedagogical training of teachers in Higher Education: Findings from the Centre for Excellence in Teaching (CET@UPT) - Fernandes, Sandra (2019)
Promoting quality teaching and learning is at the heart of the mission and goals of any Higher Education Institution. At Portucalense University (UPT), a private higher education institution, located in the north of Portugal, this goal has been strengthened by the creation of a Centre for Excellence in Teaching (CET}, launched by the hands of the Vice Rectory. This structure aims to promote academic staff development, provide pedagogic training for teachers, create pedagogical resources and enhance the dissemination of best practices and teaching quality at UPT. One of the main activities organized by CET is pedagogic training sessions for academic staff. These sessions are designed, organized and developed according to teachers‘ individual motivations, interests and needs. This paper describes part of the change process carried out at UPT, in terms of the development of student-centred pedagogical approaches and active learning methods. Results from the implementation of the first activities developed by the CET reveal a positive participation and involvement of academic staff in training sessions, according to data collected from teachers, at the end of the training sessions. Teachers showed interest in developing active learning strategies and openness to change their teaching practices, but they were also aware of the difficulties and challenges which these approaches require. The impact of the pedagogical training sessions, carried out in the year 2017/2018, for all teachers at UPT, will also be analysed and discussed in the paper.